Valorization of 3D/4D models of disappeared or ruined heritage sites in 3D modeling environments - M. Koehl; J.-E. Heitz; E. Sommer; M. Fuchs (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
3D is an increasingly common tool in many fields, including archaeology. It allows creating what no longer or almost no longer exists based on many types of information: archaeological excavation, plans, photographs, archaeological or historical hypothesis and many others. 3D is a tool of popularizing knowledge by making it more visual (photorealistic renderings of 3D restitutions and virtual reality), appreciable in a targeted context, and even by making it palpable (3D printing). By associating 3D representations/modelling tools and archaeology, we then move to 4D, integrating the notion of time and allowing people to travel through the centuries in a simple and playful way. This study shows the aspect of valuation of archaeological 3D data through 3D textured and animated restitutions, put in their current urban context. The use of 3D modelling and animation software makes it possible to give a digital and virtual appearance and consistency to historical and heritage sites. These models allow for the restoration of shapes and dimensions, and their placement within a historical context. To help users better project themselves, it is also interesting to place them in current urban contexts. But a model is not always enough on its own, we must find ways to make them visible, to make them understandable, and to promote them to neophyte audiences on the one hand, but also to make them accessible to expert audiences such as historians and archaeologists in the other hand. To illustrate the point, we used modelling projects on a Roman Castellum and a castle of the Renaissance period, both located in Horbourg-Wihr, Alsace, France. We also use models of Rhine castles carried out as part of an Interreg VI project – Châteaux Rhénans – Burgen am Oberrhein (Interreg, 2024).